Quality of life among adolescent survivors of childhood cancer - Abdullah, Wan Ariffin; Yubbu, Putri (LAP Lambert Academic Publishing, 2018)
Over the past few decades, there has been a dramatic improvement in the long-term survival of childhood cancer patients as a result of advancement in pediatric oncology management. Previously the length of survival is used as the primary outcome evaluated in oncology treatment research, but it is now widely accepted that the quality of survival is as important as the quantity of survival. The severely toxic chemotherapy must be evaluated for its detrimental impact as well as its survival benefit. The improvement in survival rate has placed an increasing emphasis on quality of life in childhood cancer survivors. This book provides knowledge and information on the quality of life among adolescent survivors of childhood cancer, rated by survivors and their caretakers using PedsQL Generic scoring. The analysis should help shed some light on the quality of life of young survivors of childhood cancer and will be especially useful to professionals in paediatric oncology or anyone who is interested in the quality of life study in adolescent or to the caretakers of cancer patients.